AGAMA DALAM PRAKTIS BUDAYA (SUATU TINJAUAN SOSIOLOGI AGAMA) - Astari Putri, Ni Nyoman Dewi (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2021)
From the perspective of religion and culture, the phenomena found in the society especially humansâ€™ life are closely related to one another. This phenomenon is sometimes misunderstood by some people who do not understand how to place religious and cultural positions in people's lives. In human life, religion and culture do not stand alone or stand by themselves, both have a very close relationship in their dialectics; aligned to create and then negate each other. Religion is a guideline for human life that is used as a reference in living their life, while culture is a habit or way of human life that is created by humans themselves from the results of creativity, feeling, and intention given by God. Religion and culture influence each other. Religion affects the culture, community groups, and ethnic groups. However, culture tends to be fickle. This relationship has implications for the authenticity of religion, resulting in different interpretations. Religion is an idea that is idolized in every social action so that society is always in balance and order of a stable system and structure. This condition can be expected to give rise to a serene and peaceful social life in which the function of religion becomes important and dominant. In this way, religion in turn truly places itself as a regulator of the traffic of social obligations through its commands and prohibitions, and in it, society cannot refuse it. The point is that in recent times, since the 20th century, religion has become an attractive object for scientists and culture.Â